Cancer incidence estimation method: an Apulian experience. (September 2017) - Nannavecchia, Anna M.; Rashid, Ivan; Cuccaro, Francesco; Chieti, Antonio; Bruno, Danila; Burgio Lo Monaco, Maria G.; Tanzarella, Cinzia; Bisceglia, Lucia
Abstract : The Cancer Registry of Puglia (RTP) was instituted in 2008 as a regional population-based cancer registry. It consists of six sections (Foggia, Barletta-Andria-Tran, Bari, Brindisi, Lecce, and Taranto) and covers more than 4 000 000 inhabitants. At present, four of six sections have received accreditation by AIRTUM (53% of regional population). To point out possible regional geographic variability in cancer incidence and also to support health services planning, we developed an original estimation method to ensure a complete territorial coverage. Incidence data of the four accredited RTP sections for the shared incidence period 2006–2008, the 2001–2009 hospitalization regional data, and 2006–2009 mortality data were considered. To take into account specific health features of different provinces, we performed an estimate of cancer incidence rates of nonaccredited sections using a combination of accredited sections rates and a factor that combines mortality and hospitalization ratios available for all the sections. Finally, we validated the method and we applied it to estimate regional cancer rates as the population-weighted average of accredited sections and nonaccredited sections adjusted rates. The validation process shows that estimated rates are close to real incidence data. The most frequent neoplasms in Apulia are breast (direct standardized rates 96.8 per 100 000 inhabitants), colon–rectum (36.6), and thyroid cancer (25.3) in women and prostate (70.2), lung (68.4), and colon–rectum cancer (52.2) in men. This method could be useful to assess the cancer incidence when complete cancer registration data are not available, but hospitalization, mortality, and neighbouring incidence data are available.